Distal Radius Fracture Pattern Correlates with Pronator Quadratus Injury Severity - Murgai, Rajan; Ghali, Miriyam; Minaie, Arya; Martin, Anthony; Dodds, Seth D. (Journal of Wrist Surgery, 2025)
The purpose of this study was to determine if the distal radius fracture pattern is associated with the degree of pronator quadratus (PQ) injury in distal radius fractures that underwent open reduction internal fixation.A retrospective review of patients with distal radius fractures who underwent open reduction internal fixation at a single institution through a standard volar approach was performed, yielding 148 patients. The extent of PQ injury was graded for each fracture intraoperatively (type 1: intact PQ with no visible muscle damage, type 2: transverse tear through the muscle at the level of the fracture site, and type 3: muscle damage and tears in multiple planes). The fractures were classified according to the Orthopaedic Trauma Association (OTA) classification of distal radius fractures. Thirty-seven patients with an intact PQ (type 1) were compared with 111 patients with an injured PQ (types 2 and 3).Partial-articular fractures were associated with less severe PQ injury (type 1 PQ injury: partial-articular 50.0%, extra-articular 25.0%, complete-articular 21.3%, p = 0.040). Volar fracture angulation was protective for PQ injury (type 1 PQ injury: volar 50.0% vs. dorsal 17.0%, p = 0.0001). In dorsally displaced fractures, increased dorsal translation was associated with more severe PQ injury (type 1 PQ injury: 3.9 ± 2.9 mm, type 2 PQ injury: 6.5 ± 4.7 mm, p = 0.006). Age, sex, dorsal tilt, and mechanism of injury were not associated with PQ injury severity.Distal radius fracture angulation, OTA fracture classification, and millimeters of dorsal translation correlate with the degree of PQ injury.Level IV.
Keywords: pronator quadratus injury; distal radius fracture; distal radius fracture classification; pronator quadratus injury repair